The effects of intramolecular and intermolecular coordination on (31)P nuclear shielding phosphorylated azoles - Chernyshev, Kirill A (Magnetic resonance in chemistry : MRC, 2012)
Copyright © 2012 John Wiley & Sons, Ltd.